Implementasi Sport Scince pada Unit Kegiatan Mahasiswa Bola Voli Universitas Ngudi Waluyo - Aristiyanto, Aristiyanto; Sukarno, Sukarno (UNIVERSITAS NGUDI WALUYO, 2021)
The development of the achievements of the Ngudi Waluyo University (UNW) volleyball Student Activity Unit (UKM) must be done using all efforts and abilities to reach the final limit in this case through the Sport Science approach for UNW volleyball UKM members. Through this programme, it is expected to be able to answer problems related to the extent of coaching capacity through training programs and injury management. This community service program is in the form of assistance for members of the Volleyball Student Activity Unit at Ngudi Waluyo University. This activity is aimed at improving the ability of UNW volleyball UKM achievement development related to the dominant physical condition of volleyball through sports training programs and its supporting factors in the form of injury management forathletes (Volleyball UKM members). The method used in this community service is starting from field observations, education and mentoring for training programs and assistance with injury management for UNW volleyball UKM athletes, to be able to improve their physical condition in supporting their performance during training and during competitions (competitions). This community service was carried out for four months, including initial observations to raise existing problems and then reviewed for problem solving, continued with initial seminars and preparations, training (theory and practice), final seminars and reporting. The training was held with theoretical material: a) identification and handling of injuries to volleyball athletes,b) Volleyball athlete training programs. Practical training in the form of improving injury management skills and, practicing making exercise programs. Based on the results of observations during the activity, the following results were shown: 1) participants were enthusiastic during the activity seen from the amount of feedback between participants and resource persons, 2) participants were active in telling training experiences and injuries they had experienced, 3) participants were very cooperative in carrying out injury management practices. Based on the results of this activity, it can be concluded that training on the implementation of sports sciences can improve knowledge and skills for members of the Volleyball UKM at Ngudi Waluyo University.ABSTRAKPembinaan prestasi Unit Kegiatan Mahasiswa (UKM) bola voli Universitas Ngudi Waluyo (UNW) harus dilakukan dengan menggunakan segala usaha serta kemampuannya hingga mencapai batas akhir dalam hal ini melalui pendekatan Sport Science bagi mahasiswa UKM bola voli UNW. Melalui pengabdian ini diharapkan dapat menjawab permasalahan terkait sejauh mana kapasitas pembinaan melalui program latihan dan penanganan cedera. Program pengabdian kepada masyarakat ini berupa pendampingan bagi anggota Unit Kegiatan Kemahasiswaan Bola Voli Universitas Ngudi Waluyo. Kegiatan ini ditujukan untuk meningkatkan kemampuan pembinaan prestasi UKM bola voli UNW terkait dengan faktor kondisi fisik dominan olahraga bola voli melalui program latihan olahraga berikut faktor pendukungnya berupa penatalaksanaan penanganan cedera bagi atlet (anggota UKM Bola Voli). Metode yang digunakan dalam pengabdian kepada masyarakat ini adalah dimulai dari observasi lapangan, edukasi dan pendampingan program latihan dan pendampingan penanganan cedera bagi para atlet UKM bola voli UNW, untuk dapat meningkatkan kondisi fisik dalam mendukung penampilan saat berlatih maupun pada saat pertandingan (kompetisi). Pengabdian kepada masyarakat ini dilakukan selama empat bulan, meliputi observasi awal untuk memunculkan masalah yang ada dan kemudian dikaji untuk diberikan pemecahan masalah, dilanjutkan seminar awal dan persiapan, pelatihan (teori dan praktik), seminar akhir dan pelaporan. Pelatihan yang diselenggarakan dengan materi teori: a) identifikasi dan penanganan cedera pada atlet bola voli, b) Program latihan atlet bola voli. Pelatihan praktik berupa peningkatan keterampilan penanganan cedera dan, praktik membuat program latihan. Berdasarkan hasil pengamatan selama kegiatan berlangsung, menunjukkan hasil sebagai berikut: 1) peserta bersemangat dan antusias selama mengikuti kegiatan dilihat dari banyaknya umpan balik antara peserta dan narasumber, 2) peserta aktif dalam menceritakan pengalaman latihan dan cedera yang pernah dialami, 3) peserta sangat kooperatif dalam melaksanakan praktik penanganan cedera. Berdasarkan hasil kegiatan ini dapat disimpulkan bahwa pelatihan implementasi sport sciences dapat meningkatkan pengetahuan dan keterampilan bagi anggota UKM Bola Voli Universitas Ngudi Waluyo.